Суб’єкт, метод пізнання, картина соціального світу в класичній, некласичній, постнекласичній соціології - Отрешко, Н. (Социология: теория, методы, маркетинг, 2009)
The specificity of transition from the classics to the non-classics, and to the post non-classics in the sociological theory is analyzed in the article. There are postulated the main principles of the classic, non-classic and post-non-classic paradigms from the philosophical point of view. On this basis, the author states general definitions of the (1) subject, (2) cognitive method, and (3) social world pattern as methodological grounds of sociological episteme. In conclusion, two ways of analysis of social reality — transcendental and immanent — are considered as examples of realization of classic and non-classic paradigms in the contemporary sociological theory.